Das KOMMA-Korpus und seine vielseitige Nutzbarkeit: Die deutsche Standardvarietät in Südtirol - Leonardi, Mara Maya Victoria (Linguistik Online, 2023)
This paper outlines the construction of the KOMMA corpus and the presentation and analysis of selected case studies. The paper contains written and oral data from young adults attending the final year of a German-language high school in South Tyrol. In addition to describing the data collection and the methods used, the paper will also go into more detail about the data processing (transcription, normalisation, lemmatisation and POS tagging). Finally, some research results illustrate the usability of the corpus, with selected case studies from the field of word formation and lexis being presented.